The transformation of the eastern German economy - Amy Elizabeth Houpt (Intereconomics, 1995)
The eastern German economy has experienced a great deal in the five years since German reunification: an unexpectedly profound collapse following the Monetary, Economic and Social Union of July 1990; a massive loss of jobs with resulting social and political consequences; and an increasingly stable economic recovery. In which branches is recovery most dynamic? Where does the structural transformation seem to be leading? And which branches have the best chances of self-sustained growth in the future? This short analysis attempts to answer these questions, to demonstrate the different trends among the branches of the economy and thereby to underscore the differentiation within the economic transformation process in the new Länder.
Keywords: 330